2018
DOI: 10.2355/isijinternational.isijint-2018-283
|View full text |Cite
|
Sign up to set email alerts
|

<i>In-situ</i> Analysis and Numerical Study of Inclusion Distribution in a Vertical-bending Caster

Abstract: Based on a fast-detection platform (FDP) founded by us, an in-situ measurement of inclusion distribution in slab is successfully performed. The inclusion distribution is obviously asymmetry and non-uniform. Specially, due to the structure differences in the vertical and bending part of a slab caster, the inclusion distribution in these two parts are quite different: In the vertical part, the inclusions entrapped in the outer arc is much more than that in the inner arc, while in the bending part, the inclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The dimensions of the current water model, densities of water, and oil used in the current work are substituted in the Equation for calculating the dimensionless open‐eye area. Li et al also measured the dimensionless open‐eye area using the model developed by Krishnapisharoday et al The results of the current work are also shown in Figure . This indicates that the open‐eye area obtained by the present model may be somewhat higher compared to the literature data.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…The dimensions of the current water model, densities of water, and oil used in the current work are substituted in the Equation for calculating the dimensionless open‐eye area. Li et al also measured the dimensionless open‐eye area using the model developed by Krishnapisharoday et al The results of the current work are also shown in Figure . This indicates that the open‐eye area obtained by the present model may be somewhat higher compared to the literature data.…”
Section: Resultssupporting
confidence: 60%
“…Nondimensional eye area versus modified Froude number; K&I = Krishnapisharody and Irons and L&L = Li and Li …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations